The influence of work-family conflict, family-work conflict, and the work environment on the job satisfaction of teachers and district elementary school employees - Wazirman Wazirman; Elmiati Elmiati; Mike Agnes (Global Econedu, 2022)
This study aims to see the effect of (1) Work-family conflict on the job satisfaction of teachers and employees of SDN Koto Baru, Kota Sungai Penuh sub-district (2) Family-work conflict on job satisfaction of teachers and employees of SDN Koto Baru, Kota Sungai Penuh sub-district (3)The work environment on the job satisfaction of teachers and employees of SDN Koto Baru, Kota Sungai Penuh District (4) work-family conflict, work-family conflict and work environment have a joint effect on the job satisfaction of teachers and employees of SDN Koto Baru, Kota Sungai Penuh District. The population in this study is all 54 teachers and employees of SDN Koto Baru, Kota Sungai Penuh District. Technique of determining the number of samplestaken as respondents using total sampling. Resultsthis study shows that (1)Work-family conflict has a negative significant effect on the job satisfaction of teachers and employees of SDN Koto Baru, Kota Sungai Penuh sub-district (2) Family-work conflict has a negative effect on the job satisfaction of teachers and employees of SDN Koto Baru, Kota Sungai Penuh District (3)Work environment provide a positive influence on the job satisfaction of teachers and employees of SDN Koto Baru, Kota Sungai Penuh District (4) Work-family conflict, work-family conflict and work environment jointly have a positive effect on the job satisfaction of teachers and employees of SDN Koto Baru, Kota Sungai Penuh District.